Does Digital Justice Contribute to Firm Innovation? Evidence from China’s Internet Courts - Huaxing Wang; Weiwei Li; Liangcong Fan; Yang Feng (SAGE Open)
This paper examines the impact of Internet courts on firm innovation, emphasizing the role of digital judicial protection. Using a staggered difference-in-differences (DID) approach and data from Chinese listed companies, we find that the establishment of Internet courts significantly enhances firm innovation, a result robust across multiple tests. Mechanism analysis reveals that Internet courts promote innovation by increasing firms’ willingness to innovate and accelerating digital transformation. Heterogeneity analysis highlights stronger effects in Internet-related services, industrial digitization sectors, private firms, and firms facing high litigation risks, likely due to their greater reliance on digital justice systems. These findings provide novel evidence linking digital justice systems to firm innovation and offer actionable insights for fostering innovation through judicial reforms in the digital era. JEL: K41, O32, P37.